Loperamide Abuse and Its Sequelae. (September 2020) - Strzyzewski, Lauren; Key, Phillip; Jones, Prentiss; Prahlow, Joseph A.
Abstract : Introduction: Loperamide is an opioid available over the counter and in prescription form. Loperamide functions as a μ-agonist within the enteric nervous system to slow intestinal motility. Its antidiarrheal properties and primarily peripheral activity make loperamide an important tool in the management of inflammatory bowel disease. Case Report: A 42-year-old man was found unconscious in cardiac arrest, and emergency medical personnel restored normal sinus rhythm. Family reported complaints of abdominal pain and that he "went through a lot" of loperamide. In the emergency department, the patient exhibited symptoms consistent with an opioid overdose. Mental status improved after administration of naloxone, an opioid antagonist. An electrocardiogram revealed a prolonged QTc interval, which progressed into Torsades de Pointes rhythm during admission. The patient succumbed from hypoxic brain injury, and there was evidence of acute pancreatitis at autopsy. Loperamide and desmethylloperamide (loperamide metabolite) were detected in blood samples. Cause of death was ruled loperamide toxicity. Discussion: Because of reduced central nervous system activity and associated euphoria at therapeutic doses, loperamide abuse is rarely reported. This case demonstrates that an overdose on loperamide can occur in patients seeking symptom alleviation, and may mimic the presentation of opioid overdose.